Code-Mixing Patterns and Viewer Perspectives in Livy Renata’s YouTube Video: A Sociolinguistic Analysis - Nisa, Lusiana Khoirun; Khazanah, Dewianti (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
This study discusses the use of code-mixing between English and Indonesian in Livy Renata's YouTube video entitled “meeting Reemar for the first time!”. Using a sociolinguistic approach, this study analyzes the types of code-mixing and viewers' perspectives on its use. This phenomenon is relevant because it reflects bilingualism in Indonesian society as well as the influence of social media in shaping linguistic perceptions in the digital era. The data used are collected from code-mixing utterances by the speakers using a content analysis method. The researchers adjust the video transcription that is displayed in English with all the speakers’ utterances, which partly use Bahasa Indonesia. The results show that insertional code-mixing is the most frequently used type, accounting for 40% of the total. Alternation comes next at 33.3%, while the remaining 26.7% includes congruent lexicalization. As stated by Geroda & Yeusy (2022), the use of insertional code-mixing means that the speakers want to show their social identity. In addition, it is also used to attract the attention of the viewers who are mostly Indonesians. With this, the use of code-mixing in the video receives positive and negative responses, which can be seen in the comments section. These viewers' responses are differentiated based on language attitudes theory, whether they are positive cognitive, positive affective, negative cognitive, or negative affective. Based on the viewers' comments, the use of code-mixing by the speakers is mostly perceived positively.